IMPROVEMENT OF THE MECHANISM FOR CRISIS MANAGEMENT OF THE ENTERPRISE - DVORNYK, Iryna; DVORNYK, Oleksii; GARAFONOVA, Olga; PALIIEV, Valerii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article explores crisis situations, their origins, influencing factors, probability of occurrence, and further development. It is noted that thorough crisis investigation and early detection of crisis indicators are crucial for companies operating in unstable and dynamic external environments.It has been established that in practice, crises can often lead to a company's bankruptcy or pose a threat to its activities due to unprofitability or lack of potential success. Considering this, the article highlights the necessity of an anti-crisis management system for companies, as even financially stable enterprises can face unexpected economic complications.The article recommends conducting a diagnosis of financial crises to identify crisis symptoms and understand their potential consequences. It proposes a system of anti-crisis measures, such as early detection of crisis situations, the development of adaptation strategies to external changes, and an effective crisis management plan. Additionally, it emphasizes the importance of risk management tools for effective enterprise management, including the use of matrix games to justify optimal decisions and strategies for overcoming crisis situations.The significance of timely diagnosis and anti-crisis management is emphasized to ensure the sustainable development of enterprises amidst uncertainty. Implementing comprehensive research and the proposed anti-crisis measures can preserve the financial stability of enterprises and successfully overcome crisis situations.
Keywords: anti-crisis management; enterprise; strategies; risk; financial resources; stability; efficiency; innovations